Isolated substorms according to magnetic measurements at Tixie during minimum solar activity - Baishev D. G.; Makarov G. A. (Solar-Terrestrial Physics, 2023)
A catalog of isolated substorms in 2016–2020 has been compiled from data on the H component of the geomagnetic field, obtained at Tixie. From the catalog data, it has been found that during this period changes in the number of substorms and the number of sunspots are well approximated by quadratic functions with minima at the end of 2017 and in the middle of 2019 respectively; during the year, disturbances more often occurred during solstice; within 24 hours, substorms more often occurred at local midnight. The intensity and duration of substorm disturbances, the duration of their expansion phase do not show a noticeable dependence on the time of occurrence; however, from average values of these parameters in hourly ranges, it has been found that the intensity takes lower values around 0–3 MLT; in the midnight sector, the duration of disturbances and the duration of their expansion phase are shorter than those in the dawn sector. Compared to the data from mid-latitude stations [Chu et al., 2015], the average duration of substorms and the duration of their expansion phase are longer.